Looking at Citizens Indonesia’s Local Wisdom through Law Sociological Approach for Efforts to Maintain the Richness of Nation - Solin, Debora Aswinda; Iryanto, Wisnu Pratama (Faculty of Law Universitas Negeri Semarang, 2019)
Local Wisdom Culture becomes a product of the historical society. Stateof Indonesia as a pluralistic country into an example of a country withthousands of culture based on the discretion of each region. Localwisdom should be understood as an effort to preserve the nation’sculture and values of our wise ancestors. Their local knowledge was theauthor feels himself at the settlement of the Author. In the villagewhere the author, there are still many people who uphold local wisdom.People still have a strong belief be a habit.